The Analysis Study of Management of Cataract in The Adult Eye Preferred Practice Pattern : A Comprehensive Systematic Review - Iffan Soffyan Ismail; Yuce Yuanita (The International Journal of Medical Science and Health Research, 2024)
Background: Cataracts, the leading cause of blindness and a major contributor to vision impairment worldwide, disproportionately affect older adults, particularly in low- and middle-income countries with limited access to eye care. While cataract surgery is a highly cost-effective intervention capable of restoring vision, the prevalence of cataracts continues to rise due to socio-economic and infrastructural challenges. To address these issues, the World Health Organization (WHO) has introduced initiatives such as the Package of Eye Care Interventions (PECI) and emphasized the need for updated, region-specific clinical practice guidelines to improve cataract management and enhance universal health coverage. Methods: This systematic review adhered to the PRISMA 2020 guidelines, focusing exclusively on full-text articles published in English between 2014 and 2024. Editorials and review articles without a DOI were excluded to ensure high-quality sources. An exhaustive literature search was conducted across reputable databases, including ScienceDirect, PubMed, and SagePub, to identify relevant studies. Result: An initial database search yielded 500 publications relevant to adult cataract management. After implementing a rigorous three-stage screening process, eight studies meeting the inclusion criteria were selected for comprehensive analysis. These studies were critically evaluated to provide an in-depth assessment of preferred practices in adult cataract management, ensuring a focused and high-quality synthesis of the available evidence. Conclusion: Management strategies for cataracts are crucial for addressing global blindness and visual impairment, focusing on early detection, early detection, and addressing global disparities to optimize surgical outcomes and patient quality of life.